Making sense of Jesus Experiences, interpretations and identities - Tolmie, Francois; Venter, Rian (Theological Explorations, 2017)
Making sense of Jesus is comprised of twelve chapters of a Christological nature, which are the result of a multidisciplinary theological research project. The aim of this book is to ascertain how, in the current cultural situation, an encounter with Jesus is determined by specific historical and personal conditions, and what the consequences of such an encounter may be.